2019
DOI: 10.1021/acsami.9b13839
|View full text |Cite
|
Sign up to set email alerts
|

Dual Role of Lithium on the Structure and Self-Healing Ability of PMMA-Silica Coatings on AA7075 Alloy

Abstract: In this work, structural and active corrosion inhibition effects induced by lithium ion addition in organic-inorganic coatings based on polymethyl methacrylate (PMMA)-silica solgel coatings have been investigated. The addition of increasing amounts of lithium carbonate (0, 500, 1000 and 2000 ppm), yielded homogeneous hybrid coatings with increased connectivity of nanometric silica cross-link nodes, covalently linked to the PMMA matrix, and improved adhesion to the aluminum substrate (AA7075). Electrochemical i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 53 publications
2
38
0
Order By: Relevance
“…Hybrid sols have been prepared using TEOS and MAPTMS in the optimum ratio [5]. Since previous studies on these type of coatings were carried out on steel-based substrates [3][4][5][6] and less on Al-based substrate [8,15], we focused this study on aluminium alloy (AA) 7075-T6 substrate. This particular alloy was chosen because it is the least corrosion resistant among alloys used in the aviation industry.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid sols have been prepared using TEOS and MAPTMS in the optimum ratio [5]. Since previous studies on these type of coatings were carried out on steel-based substrates [3][4][5][6] and less on Al-based substrate [8,15], we focused this study on aluminium alloy (AA) 7075-T6 substrate. This particular alloy was chosen because it is the least corrosion resistant among alloys used in the aviation industry.…”
Section: Introductionmentioning
confidence: 99%
“…The films with thickness between 4 μm and 6 μm present excellent adhesion to AA7075 substrate reaching values up to 28 MPa for coatings with higher Li loading [24]. The improved adhesion for lithium-rich coatings might be related to aluminum enrichment near the coating/substrate interface, suggesting a diffusion of Al from the alloy into the coating during the thermal treatment [24].…”
Section: Corrosion Inhibition By Lithium Ionsmentioning
confidence: 98%
“…As possible mechanisms, Visser et al have proposed that the release of lithium ions from the epoxy matrix forms in the defective zone a Li/Al layer (hydrotalcite class) by a conversion process [46]. In recent work, lithium carbonate (Li 2 CO 3 ) was for the first time added (500-2000 ppm) into the PMMA-silica system, and the results revealed a dual beneficial effect of lithium on the structure and self-healing ability of the coatings on the AA7075 aluminum alloy [24]. The structural analysis of the coatings showed that the changes of the smallangle X-ray scattering (SAXS) profiles imply significant modifications in the nanostructure of the silica phase for higher lithium loadings (Figure 5a).…”
Section: Corrosion Inhibition By Lithium Ionsmentioning
confidence: 99%
See 2 more Smart Citations